Avaliação das estratégias de desenvolvimento de produtos ecológicos na cadeia de transformação dos resíduos plásticos industriais - Fernandes, Michele Aragão (2011)
The survey, whose theme is the evaluation of strategies for development of green products in the chain of industrial plastic waste, is justified by the behavior change and new positioning of the companies with the environment. The paper presents a qualitative methodology with descriptive purposes and procedures of collecting literature on multiple case study. The selected companies are registered for research at the Stock FIEC Waste and Business - Federation of Industries of the State of Ceará. The present study aims to investigate whether products derived from industrial plastic waste can be classified as green, mapping the supply chain and processing of waste plastics recycling companies surveyed and analyze the process of developing products derived from industrial plastic waste in the light model Morilhas and Nascimento (2007). As a result, it was found that not all products derived from industrial plastic waste are considered according to the ecological model, because these products must meet all the criteria set out stages and environmental life cycle of an environmentally friendly product. However, this model should not be considered a unique assessment tool to classify an ecological product, but consider it as complementary to theoretical frameworks for such analysis.